ROLE INFORMATIVELY COMMUNICATION ENVIRONMENTS IN DEVELOPMENT OF DIVERGENCE THOUGHT OF FUTURE TEACHERS OF MATHEMATICS (Journal of Information Technologies in Education (ITE), 2011)
Speech goes in the article about the role of information technologies in creation of informatively communication environments in development of divergence thought of future teachers of mathematics.
Keywords: creative tasks; divergence thought; information technologies; informative space